Participation in athletics for life - the role of the European U20 and U23 championships (2016)
The focus of this study was the important role played by the U20 and U23 Championships in helping to keep young athletes involved in the sport of athletics as senior athletes, which thus benefits the wider athletics community. This study has shown that the European U20 and U23 Championships improve participation rates as junior athletes move into the senior rankings. The U23 championships were particularly effective in maintaining participation between the ages of 25 and 29. Men and women did not differ greatly, although certain events had longer participation rates (especially the throws). Additionally, maintaining junior athletes` involvement in the sport might be more difficult in very large and small nations where even being good enough to be selected for age group championships is a considerable challenge. Although the focus of this study was on athletes who had appeared in the World Junior Rankings, this was predominantly because of the ease with which these athletes could be tracked over the course of the subsequent 10 years; supporting junior athletes of all abilities is important from the point of view of remaining competitive for life and, by extension, fit for life.